Development of pineapple waste pellets and In vitro digestilibility study for herbivore - Zainuddin, Muhammad Fakhri (2015)
Pineapple agro-waste, the residue produced during harvesting or processing activities,is widely available around the world. After harvesting, most pineapple residue is disposed of and serves as fertiliser, or is burnt in an open field. However, these methods are not only ineffective, but also contribute to pollution. The objectives of this research is to provide value added products from pineapple biomass. Three different varieties of pineapple plant waste were chosen, namely Josapine, Moris and MD2. The physicochemical properties of these plants were determined by separating the leaves and stem from the plant. The analysis was done by using Thermogravimetric Analysis (TGA) and proximate analysis to determine the cell wall structure (hemicellulose, cellulose and lignin), and also the proximate content (moisture content, crude protein,crude fat, ash, crude fibre, carbohydrate). Proximate analysis showed that the nutrient content is available in the leaves and stems of the pineapple plant of the different varieties with almost similar values. Therefore, one of the possible ways to manage pineapple residues is by converting them into animal feed by a densification process. Densification of biomass feedstock, such as compaction and extrusion, can increase bulk density, improve storability, reduce transportation costs, and enable easier handling with proper storage equipment. The whole pineapple plant waste was converted to powder form, then extruded and also compacted by using an extruder and a compacter with five levels of moisture content (30 %, 35 %, 40 %, 45 % and 50 %). The findings of this study suggest that the moisture content from the extrusion process had no significant effect on the physical aspect of the pellet, except for the compaction process. An in vitro gas production was tested to the pellets to find the percentage of digestibility in rumen. This technique was continuously measured by incubating samples in buffered rumen obtained from a fistulated cow for 72 hours. Cumulative gas production, chemical composition (OMD, SCFA, NEl, ME), rate of digestion of material and the pH of the rumen fluid were estimated. The chemical analysis and nutritional value of these pellets showed that they possess similar values with no significant difference (p > 0.05). However, pellets from the compaction process showed that they have a high digestibility rate with a significant effect (p < 0.05) compared to the pellets from the extrusion process. Thus, these pellets have the potential to become a good source of fibre for ruminants.